Preoperative Psychological Preparation of Children - Güleç, Ersel (Turk J Anaesthesiol Reanim, 2015)
Surgery and anaesthesia are significant sources of anxiety for children. In the preoperative period, reducing anxiety helps in preventing the negative consequences that may occur after surgery. The predetermined high-risk children in terms of the development of anxiety play an important role in reducing the negative consequences. Recently featured approaches are modelling and coping techniques, although many techniques are used in the preoperative psychological preparation. The use of computer programs in this area may facilitate important achievements, and it needs to support new studies to be performed.